2015
DOI: 10.1073/pnas.1512325112
|View full text |Cite
|
Sign up to set email alerts
|

Correlating steric hydration forces with water dynamics through surface force and diffusion NMR measurements in a lipid–DMSO–H 2 O system

Abstract: Dimethyl sulfoxide (DMSO) is a common solvent and biological additive possessing well-known utility in cellular cryoprotection and lipid membrane permeabilization, but the governing mechanisms at membrane interfaces remain poorly understood. Many studies have focused on DMSO-lipid interactions and the subsequent effects on membrane-phase behavior, but explanations often rely on qualitative notions of DMSO-induced dehydration of lipid head groups. In this work, surface forces measurements between gel-phase dipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 50 publications
8
62
0
Order By: Relevance
“…made in the two reports [6,9]. The experimental studies using SFA and ODNP measurements [6,9] observed (i) a decrease of membrane repulsion [39] and (ii) enhanced local diffusivity of surface water in the presence of DMSO (X DMSO < 10 mol%), respectively.…”
Section: /Dmentioning
confidence: 94%
See 4 more Smart Citations
“…made in the two reports [6,9]. The experimental studies using SFA and ODNP measurements [6,9] observed (i) a decrease of membrane repulsion [39] and (ii) enhanced local diffusivity of surface water in the presence of DMSO (X DMSO < 10 mol%), respectively.…”
Section: /Dmentioning
confidence: 94%
“…The experimental studies using SFA and ODNP measurements [6,9] observed (i) a decrease of membrane repulsion [39] and (ii) enhanced local diffusivity of surface water in the presence of DMSO (X DMSO < 10 mol%), respectively. The authors surmised that the competition between DMSO and surface hydration water on the interaction with lipid head-groups led to weakening of the strength of the cohesive water network hydrating the membrane headgroups, and thus enhancing surface water diffusivity and dehydration of the bilayer surfaces.…”
Section: Cc-by-nc-ndmentioning
confidence: 99%
See 3 more Smart Citations